Physical exercise and mitochondrial function: New therapeutic interventions for psychiatric and neurodegenerative disorders - Sun, Lina; Liu, Tianbiao; Liu, Jingqi; Gao, Chong; Zhang, Xiaohui (Frontiers in Neurology, 2022)
Psychiatric and neurodegenerative diseases, including major depression disorder (MDD), bipolar disorder, and Alzheimer's disease, are a burden to society. Deficits of adult hippocampal neurogenesis (AHN) have been widely considered the main hallmark of psychiatric diseases as well as neurodegeneration. Herein, exploring applicable targets for improving hippocampal neural plasticity could provide a breakthrough for the development of new treatments. Emerging evidence indicates the broad functions of mitochondria in regulating cellular behaviors of neural stem cells, neural progenitors, and mature neurons in adulthood could offer multiple neural plasticities for behavioral modulation. Normalizing mitochondrial functions could be a new direction for neural plasticity enhancement. Exercise, a highly encouraged integrative method for preventing disease, has been indicated to be an effective pathway to improving both mitochondrial functions and AHN. Herein, the relative mechanisms of mitochondria in regulating neurogenesis and its effects in linking the effects of exercise to neurological diseases requires a systematic summary. In this review, we have assessed the relationship between mitochondrial functions and AHN to see whether mitochondria can be potential targets for treating neurological diseases. Moreover, as for one of well-established alternative therapeutic approaches, we summarized the evidence to show the underlying mechanisms of exercise to improve mitochondrial functions and AHN.